Dinámica y fomento del aprendizaje organizacional mediante el uso del Balanced Scorecard (Ingenieria y Universidad, 2000)
This paper presents the results of a research project on the construction of a generic model of the Balanced Scorecard. The main objective of the model was to encourage organizational learníng in the users organizations. Such a model was built from a set of well defined criteria and using the theory and methodology of systems dynamics. Results of the model applied in three different organízatíons are shown.